Verbalization of the concept of “hearing” in Slavic languages - Pedchenko, Liudmyla (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The purpose of this study is to identify the most productive cognitive-nominative models that form the core of the nominative field of the concept “hearing” in Slavic languages. The object of the study is the Slavic names of auditory perception. The subject of the study is the onomasiological structure of these names.As a result of the research, it was established that the nomination models, according to which the concept of “hearing” is verbalized in Slavic languages, are few. Modern Slavic nominations of auditory perception belong to the all-Slavic vocabulary and have Proto-Indo-European roots.The main Slavic name for the ability to hear – слух – is a verbal formation that implements the nominative model: ‘action’ > ‘ability to perform an action’. The semantic development of this lexeme (‘voice’ > ‘ability to hear’), the etymological connection of the lexemes слух, слава and слово, the combination of the meanings of ‘speak’ and ‘hear’ in the semantics of the Proto-Slavic verb *slūti indicate that this root in the Proto-Slavic language, the ability to perceive not just sounds, but the sounds of human speech was first noted.From another Slavic verb denoting auditory sensations – чути – the abstract name of auditory perception was not formed in Slavic languages, which seems to be connected with the semantic syncretism of the ascending verb, which can be used in relation to different perceptual modes (touch, smell, hearing, etc.) or act as an undifferentiated designation of sensation.When using the lexeme ухо in the sense of ‘hearing’, the model is implemented: ‘an organ performing a certain function’ > ‘function’, but this model is not productive in Slavic languages (recorded only in Russian). Since for the lexeme ухо the meaning ‘ability to perceive’ is not characteristic, in Slavic languages there are no names of deafness formed according to the model: ‘absence of an organ performing a function’ > ‘absence of a function’ (in contrast to the names of blindness, for which this model is productive).From the onomasiological point of view, it is possible to ascertain the presence of two main cognitive features that influence the nature of the verbalization of the concept of “hearing” in Slavic languages: first, the obvious initial connection of auditory perception with human speech activity (the conceptualization of the human ability to hear was formed in connection connected with the development of articulate speech), and secondly, the semantic syncretism of perceptive vocabulary, which is based on the interaction of different perceptual modes of a person (the phenomenon of synesthesia).